Lipedema and adipose tissue: current understanding, controversies, and future directions - Rabiee, Atefeh (Frontiers in Cell and Developmental Biology, 2025)
Lipedema is a chronic disorder characterized by the symmetrical accumulation of subcutaneous adipose tissue, predominantly affecting women. Despite increasing recognition, the pathophysiological mechanisms underlying adipose tissue dysfunction in lipedema remain incompletely understood. This mini review combines current knowledge about adipose tissue biology in lipedema, highlighting recent discoveries, ongoing controversies, and future research directions. A comprehensive literature review was conducted focusing on adipose tissue-related research in lipedema with emphasis on pathophysiological mechanisms, cellular composition, and therapeutic implications. Recent studies reveal that lipedema adipose tissue exhibits distinct characteristics, including M2 macrophage predominance, stage-dependent adipocyte hypertrophy, progressive fibrosis, and altered lymphatic/vascular function. The inflammatory profile differs markedly from obesity, with an anti-inflammatory M2-like macrophage phenotype rather than the pro-inflammatory M1 response seen in classic obesity. Emerging evidence suggests lipedema may represent a model of “healthy” subcutaneous adipose tissue expansion with preserved metabolic function despite increased adiposity. Current research proposes menopause as a critical turning point, driven by estrogen receptor imbalance and intracrine estrogen excess. Lipedema represents a unique adipose tissue disorder distinct from obesity, characterized by specific cellular and molecular signatures. Current research gaps include the need for validated biomarkers, standardized diagnostic criteria, and targeted therapeutics. Future research should focus on elucidating the molecular mechanisms driving adipose tissue dysfunction and developing precision medicine approaches.